Protein-protein docking by simulating the process of association subject to biochemical constraints - Motiejunas, Domantas; Gabdoulline, Razif; Wang, Ting; Feldman-Salit, Anna; Johann, Tim; Winn, Peter J.; Wade, Rebecca C. (Proteins, structure, function, and bioinformatics, 2008)
We present a computational procedure for modeling protein–protein association and predicting the structures of protein–protein complexes. The initial sampling stage is based on an efficient Brownian dynamics algorithm that mimics the physical process of diffusional association. Relevant biochemical data can be directly incorporated as distance constraints at this stage. The docked configurations are then grouped with a hierarchical clustering algorithm into ensembles that represent potential protein–protein encounter complexes. Flexible refinement of selected representative structures is done by molecular dynamics simulation. The protein–protein docking procedure was thoroughly tested on 10 structurally and functionally diverse protein–protein complexes. Starting from X‐ray crystal structures of the unbound proteins, in 9 out of 10 cases it yields structures of protein–protein complexes close to those determined experimentally with the percentage of correct contacts >30% and interface backbone RMSD <4 Å. Detailed examination of all the docking cases gives insights into important determinants of the performance of the computational approach in modeling protein–protein association and predicting of protein–protein complex structures. Proteins 2008. © 2008 Wiley‐Liss, Inc.